The Correlation between the Gut Microbiota of Endoclita signifer (Lepidoptera, Hepialidae) Larvae and Their Host Preferences - Jintao Lu; Xiaoyan Su; Zhende Yang; Ping Hu (Insects, 2023)
Insects’ gut microbiota plays a crucial role in their host selection, adaptation, and plasticity. This study explored the impact of gut bacteria on the adaptation of host selection under different stresses (diverse feeding preferences and no feeding preferences). The seventh instar E. signifer larvae were artificially transferred from the most-selected host E. grandis × E. urophylla (Es) to more preferred hosts, M. apelta (Ma), as well as the non-preferred host, B. papyrifera (Bp). We then obtained the larval gut of three different feeding preference hosts. The gut bacterial DNA was sequenced and analyzed based on 16S rRNA. There were significant differences in the composition of dominant gut bacteria between Es with Ma and Bp, but without significant differences between Ma and Bp. In the process, Burkholderia and Microbacillus with degrading pesticides had significant changes, and Enterococcus with insect gut probiotics also had significant changes. The presence of enterococcus may be one of the main causes of intestinal microbiota changes before and after host transfer. Notably, when the feeding of E. signifer changes, the complex connections that exist between gut bacteria also change. Additionally, there was a negative correlation between the feeding preferences of E. signifer and the metabolic functions of their gut bacteria. This study provided a theoretical basis for the prediction and use of gut bacteria to interfere with the feeding of E. signifer.